Antibacterial Activity of Jatropha curcas (Linn) Leaves Extract a gainst Vibrio harveyi and Aeromonas hydrophila - Nasrullah Bai Arifin; Imas Marthapratama; Ellana Sanoesi; Arief Prajitno (Universitas Gadjah Mada, 2017)
The use of natural products as an antimicrobial agent is an alternative way in the treating drug-resistant pathogens. A. hydrophila and V. harveyi are pathogenic bacteria both in freshwater and marine culture, respectively. Physic nut (Jatropha curcas, Linn) has been known as an herbal plant that has an antibacterial agent. The purpose of this study was to analyze inhibition ability of an extract of physic nut leaves on the growth of V. harveyi and A. hydrophila. In this study, water extract of physic nut leaves was determined to evaluate the antibacterial activity against V. harveyi and A. hydrophila using the Minimum Inhibitory Concentration Test (MIC) and Paper Disk Diffusion Method. The smallest concentration on the MIC was 0.10 g/ml for A. hydrophila and 0.15 g/ml for V. harveyi, respectively. The Paper Disk Diffusion Method used difference concentrations (0.10 g/ml; 0.15 g/ml; 0.20 g/ml; 0.25 g/ml; 0.30 g/ml; 0.35 g/ml; dan 0.40 g/ml) and Control (0 g/ml). The concentration of 0.35 g/ml had the highest inhibition zone diameter in 11.3±0.2 mm for A. hydrophila and 0.40 g/ml had the highest inhibition zone in 11.2±0.3 mm for V. harveyi. The result showed that water extract of physic nut leaves was able to inhibit both tested bacteria.